Outcomes of pulpotomy using calcium silicates in permanent teeth with symptomatic irreversible pulpitis: A systematic review and meta-analysis - Fahd Aljarbou; AlWaleed Abushanan; Ahmed A. AlMokhatieb; Mohammed Mustafa; Mohammad Khursheed Alam; Hadi Mohammed Alamri (Saudi Endodontic Journal)
The decision making process for managing irreversible pulpitis in permanent teeth often involves choosing between pulpotomy and root canal treatment, with clinicians exercising discretion. This systematic review and meta-analysis aim to evaluate the efficacy of calcium silicate based pulpotomy in treating symptomatic permanent teeth with irreversible pulpitis. A comprehensive search across PubMed, Google Scholar, and SCOPUS databases yielded 482 articles. From this pool, 169 articles underwent further scrutiny. Following data filtration, presentation, and analysis, a meta-analysis was conducted using RevMan 5 software. Eleven articles were ultimately selected based on predefined inclusion and exclusion criteria. This meta-analysis revealed that calcium silicate based pulpotomy, employed in treating irreversible pulpitis cases, exhibited notable success rates ranging from 75% to 90% over a period of 15 years across most of the included studies. The majority of studies integrated into this systematic review reported successful outcomes for teeth with symptomatic irreversible pulpitis undergoing pulpotomy with the utilization of calcium silicate. Nonetheless, further research is necessary to delineate the precise roles of calcium silicate based pulpotomy in managing this condition.